Analisis Jumlah Tenaga Kerja Optimal Dengan Metode Work Load Analysis (WLA) di PT. RSI - Darsini; Andika Maulana; Budi Wibowo (Journal of Applied Mechanical Engineering and Renewable Energy, 2021)
Workload of employees at PT. RSI in the pressing department is still low, because in the pressing section the division of work for each employee is not optimal or evenly distributed. So it is necessary to do research with the title Analysis of the Optimal Workforce at PT. RSI. The method used for testing the optimal amount of load is the Work Load Analysis (WLA) method, which aims to calculate the optimal workload and number of workers at PT. RSI. The sample in this study were 15 employees in the pressing department which were divided into 4 sections, where section 1 had 4 employees, section 2 had 4 employees, section 3 had 4 employees, and section 4 contained 3 employees. The results of this study indicate that the workload before the research in section 1 was 52% to 70%, part 2 from 51% to 68%, part 3 from 56% to 75%, and part 4 still 71% because there was no reduction in labor., because the workload in section 4 is optimal. So the optimal number of workers in the pressing department is 3 employees in section 1, 3 employees in section 2, 3 employees, and 4 still 3 employees.